Interaction of Food Production Household Energy and Environmental Change in Hill Environments: A Simulation Approach - Baskota, Mahesh (Himalayan Review, 2011)
Not available. Key words: Food Production; Energy and Environmental Change; Hill Environments The Himalayan Review Vol. 11, 1979 Page: 45-64 Uploaded Date: April 5, 2011